Design of Primers for Evaluation of Lactic Acid Bacteria Populations in Complex Biological Samples - Hou, Qiangchuan; Bai, Xiaoye; Li, Weicheng; Gao, Xu; Zhang, Faming; Sun, Zhihong; Zhang, Heping (Frontiers in Microbiology, 2018)
Lactic acid bacteria (LAB) are important for human health. However, the relative abundance of LAB in complex samples, such as fecal samples, is low and their presence and diversity (at the species level) is understudied. Therefore, we designed LAB-specific primer pairs based on 16S rRNA gene consensus sequences from 443 species of LAB from seven genera. The LAB strains selected were genetically similar and known to play a role in human health. Prior to primer design, we obtained consistent sequences for the primer-binding sites by comparing the 16S rRNA gene sequences, manually identifying single-stranded primers and modifying these primers using degenerate bases. We assembled primer pairs with product sizes of >400bp. Optimal LAB-specific primers were screened using three methods: PCR amplification, agarose gel electrophoresis and single-molecule real-time (SMRT) sequencing analysis. During the SMRT analysis procedure, we focused on sequence reads and diversity at the species level of target LAB in three fecal samples, using the universal bacterium primer 27f/1492r as a reference control. We created a phylogenetic tree to confirm the ability of the best candidate primer pair to differentiate amongst species. The results revealed that LAB-specific primer L5, with a product size of 750 bp, could generate 3222, 2552 and 3405 sequence reads from fecal Samples 1, 2 and 3. This represented 14%, 13% and 10% of all target LAB sequence reads, respectively, compared with 2%, 0.8% and 0.8% using the 27f/1492r primer. In addition, L5 detected LAB that were in low abundance and could not be detected using the 27f/1492r primer. The phylogenetic tree based on the alignments between the forward and reverse primer of L5 showed that species within the seven target LAB genera could be distinguished from each other, confirming L5 is a powerful tool for inferring phylogenetic relationships amongst LAB species. In conclusion, L5 is a LAB-specific primer that can be used for high-throughput sequencing and identification of taxa to the species level, especially in complex samples with relatively low LAB content. This enables further research on LAB population diversity in complex ecosystem, and on relationships between LAB and their hosts.